Association study of polymorphisms in the excitatory amino acid transporter 2 gene (SLC1A2) with schizophrenia - Deng, Xiangdong; Shibata, Hiroki; Ninomiya, Hideaki; Tashiro, Nobutada; Iwata, Nakao; Ozaki, Norio; Fukumaki, Yasuyuki (BMC psychiatry, 2004)
The glutamatergic dysfunction hypothesis of schizophrenia suggests that genes involved in glutametergic transmission are candidates for schizophrenic susceptibility genes. We have been performing systematic association studies of schizophrenia with the glutamate receptor and transporter genes. In this study we report an association study of the excitatory amino acid transporter 2 gene, SLC1A2 with schizophrenia. We genotyped 100 Japanese schizophrenics and 100 controls recruited from the Kyushu area for 11 single nucleotide polymorphism (SNP) markers distributed in the SLC1A2 region using the direct sequencing and pyrosequencing methods, and examined allele, genotype and haplotype association with schizophrenia. The positive finding observed in the Kyushu samples was re-examined using 100 Japanese schizophrenics and 100 controls recruited from the Aichi area. We found significant differences in genotype and allele frequencies of SNP2 between cases and controls (P = 0.013 and 0.008, respectively). After Bonferroni corrections, the two significant differences disappeared. We tested haplotype associations for all possible combinations of SNP pairs. SNP2 showed significant haplotype associations with the disease (P = 9.4 x 10-5, P = 0.0052 with Bonferroni correction, at the lowest) in 8 combinations. Moreover, the significant haplotype association of SNP2-SNP7 was replicated in the cumulative analysis of our two sample sets. We concluded that at least one susceptibility locus for schizophrenia is probably located within or nearby SLC1A2 in the Japanese population.